2013
DOI: 10.13172/2052-7829-1-1-427
|View full text |Cite
|
Sign up to set email alerts
|

Close relationships among the seven grey matters of the limbic system and basal ganglia with regard to the phosphorus content

Abstract: Introduction Our aim was to elucidate compositional changes of the brain with aging; we investigated the relationships among the seven grey matters belonging to the limbic system and basal ganglia with regard to their phosphorous content. Materials and methods After ordinary dissections were completed, the hippocampus, dentate gyrus, mammillary body, amygdala, caudate nucleus, putamen and globuspallidus of the grey matter, were removed from the identical brains of the subjects. The subjects consisted of 22 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Tohno et al in his study reported that the mandible of the condyle region is one of the sexual dimorphic regions and it can be used in forensic cases [40] and this is similar to our finding. In a study, conducted on sex determination by using mandible by morphometric and morphological analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Tohno et al in his study reported that the mandible of the condyle region is one of the sexual dimorphic regions and it can be used in forensic cases [40] and this is similar to our finding. In a study, conducted on sex determination by using mandible by morphometric and morphological analysis.…”
Section: Discussionsupporting
confidence: 92%
“…The authors previously investigated age-related changes in elements by direct chemical analysis of the monkey cardiac walls [30], sinoatrial node [31], cardiac valves [32], tendon of the peroneus longus muscle [33], ligamentum capitis femoris [34], and various arteries [35][36][37][38][39][40] and found that the elements did not uniformly accumulate in various monkey tissues and organs with age. In the cardiac walls, sinoatrial nodes, cardiac valves, and coronary artery [35][36], the calcium content gradually decreased with development. Conversely, in most arteries [37][38][39][40] and the tendon of the peroneus longus muscle, the calcium content progressively increased with age.…”
Section: Table 2 Relationships Among Seven Elements In the Tcmentioning
confidence: 99%